Search for physics beyond the standard model in multilepton final states in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2020)
A search for physics beyond the standard model in events with at least three charged leptons (electrons or muons) is presented. The data sample corresponds to an integrated luminosity of 137 fb(-1) of proton-proton collisions at root s = 13 TeV, collected with the CMS detector at the LHC in 2016-2018. The two targeted signal processes are pair production of type-III seesaw heavy fermions and production of a light scalar or pseudoscalar boson in association with a pair of top quarks. The heavy fermions may be manifested as an excess of events with large values of leptonic transverse momenta or missing transverse momentum. The light scalars or pseudoscalars may create a localized excess in the dilepton mass spectra. The results exclude heavy fermions of the type-III seesaw model for masses below 880 GeV at 95% confidence level in the scenario of equal branching fractions to each lepton flavor. This is the most restrictive limit on the flavor-democratic scenario of the type-III seesaw model to date. Assuming a Yukawa coupling of unit strength to top quarks, branching fractions of new scalar (pseudoscalar) bosons to dielectrons or dimuons above 0.004 (0.03) and 0.04 (0.03) are excluded at 95% confidence level for masses in the range 15-75 and 108-340 GeV, respectively. These are the first limits in these channels on an extension of the standard model with scalar or pseudoscalar particles.
Keywords: Beyond Standard Model; Hadron-Hadron scattering (experiments); NEUTRINO MASS